(untitled) (Journal of Green Business School, 2025)
This study aims to identify the elements that boost up students’ enthusiasm for online classes conducted by a faculty member in Green University of Bangladesh. In this study qualitative methodology was employed. To dig out the online class engagement process, the students of Green University of Bangladesh were objectively targeted for collecting the information. A total of 198 samples were purposively selected for collecting quantitative data. The respondents were asked to describe their perceptions towards the factors increasing their motivation and what can be done to increase their motivation through a questionnaire comprised of structured and semi-structured questions. The findings of the study demonstrate that the learning-teaching process, teacher’s competency, student attentiveness, online learning environment, technical infrastructure, and time management impact students’ motivation for online courses. Additionally, it is stated that technological infrastructure, learning-teaching process, measurements and evaluations would boost up students’ motivation. Thus, the study has been taken up for putting suggestion for enhancing students’ motivation in participating in their online classes. J. of Green Business. Sch. Vol 6(1), Jan-Dec, 2023; pp 31-40